‘Mixt marriages’: Ethnic and religious intermarriage among German-speakers in eighteenth-century Pennsylvania - McDaniel, Marie Basile (The History of the Family, 2019)
Civil and religious authorities in eighteenth-century America grew increasingly concerned over the freedom with which young people chose their marriage partners. Correlating racial, religious and cultural similarity in marriage to a stable society, these authorities attempted to limit marriage and sexual choices by requiring parental authority for marriage, distributing permits to a select few to perform marriages, and criminalizing racial miscegenation. Eighteenth-century Pennsylvania German authorities supported this attitude because they associated ethnic and religious out-marriage with the weakening of the body and the destruction of society. My study uses the marriage and birth records of eighteenth-century Pennsylvania Germans to examine their marriage and sexual relationships. I discovered that Pennsylvania Germans overwhelmingly chose to marry other German-speakers, out of proportion with their population. By examining the then available works on marriage and procreation, I discovered that Pennsylvania Germans read works that emphasized the necessity and importance of intra-ethnic and religious sex and marriage for the health of their children. Pennsylvania Germans chose their marriage partners in alignment with their community’s attitudes towards those of other ethnicities and religions. A small data set further suggests that relationships with non-Germans occurred but rarely became formalized. This complicates what we know about the sexual and emotional revolutions in the seventeenth and eighteenth centuries; far from a linear progression of attitudes towards sex, marriage, and others, eighteenth-century Pennsylvania Germans expressed multiple, contextually-driven perspectives, and in the process they created and maintained strong ethnic communities. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Defoe; German (citizen); German-speakers; Marriage; Pennsylvania; article; child; colonial; dept.his; destruction; ethnicity; female; human; human experiment; male; marriage; peer-reviewed; pre-marital; religion